Design and Build Desktop-Based Educational Game Save The Wildlife "With Game Engine Construct 2: Design and Build Desktop-Based Educational Game Save The Wildlife "With Game Engine Construct 2 - Fajar Muhammad Sukmawijaya; Cholid Fauzi (Jurnal Mantik, 2020)
Educational Games are digital games that are designed for enrichment and education. One of the benefits of the game is as entertainment and to get players' inner satisfaction from the game. Games can also be used as a fun educational delivery tool. Educational games have other positive values ??in them, by supporting teaching and learning. In order to obtain the essence or additional knowledge for players of the game. Indonesia is a country that has a very high level of biodiversity and endemism. One of them is the diversity of fauna (animals) in Indonesia. The problem faced by animals in Indonesia today is the rampant hunting and trade of animals. If not further addressed then it is not impossible that the next few years these animals will become extinct. This is due to a lack of awareness of the importance of protecting nature and caring for protected animals. Understanding of environmental and animal care needs to be educated as early as possible. In this final project, a product in the form of the game "Save the Wildlife" is created which aims to introduce and provide information about protected animals in Indonesia. An arcade game created with the game engine Construct 2. The design method used is Collision detection, which is a method used to detect collisions or collisions between an object and other objects. It is hoped that by making this game, players, especially children, will get to know more about protected animals in Indonesia and better protect and preserve the environment of these animals.